Wolves in sheep clothing or victims of times? Discussing the immoderation of incumbent Islamic parties in Turkey, Egypt, Morocco, and Tunisia. Issue 5 (4th July 2018) - Kirdiş, Esen
ABSTRACT: This article discusses the "immoderation" of incumbent Islamic parties – defined by the pursuit of a moral agenda and by an unwillingness to compromise with the opposition – through a comparative study of four incumbent Islamic parties in the socio-politically different regimes of Turkey, Egypt, Morocco, and Tunisia. Building on literature from religion and politics, social psychology, sociology of religion, and on the inclusion-moderation hypothesis, this study argues that (1) Islamic parties' strong organizations resulted both in their success and in the absence of internal pluralism and that (2) their dominant status in the party system consolidated their majoritarian understanding of democracy. Through its discussion of "immoderation" this study aims to contribute to the interdisciplinary literature on religion and politics.